Clinical aspects of reimbursement policies for orphan drugs in Central and Eastern European countries - Jakubowski, Szczepan; Kawalec, Pawel; Holko, Przemyslaw; Kowalska-Bobko, Iwona; Kamusheva, Maria; Petrova, Guenka; Draganić, Pero; Fuksa, Leos; Männik, Agnes; Ispán, Fanni; Briedis, Vitalis; Bianchi, Ioana; et al. (Frontiers in Pharmacology, 2024)
Objectives: The aim of this study was to characterize the reimbursement policy for orphan drugs (ODs) in Central and Eastern European (CEE) countries in relation to the availability and impact of clinical evidence, health technology assessment (HTA) procedures, selected economic indicators, and drug type according to indication. Materials and Methods: A list of authorized medicines with orphan designation and information about active substance, Anatomical Therapeutic Chemical (ATC) classification, and therapeutic area were extracted from the web-based register of the European Medicines Agency (EMA). A country-based questionnaire survey was performed between September 2021 and January 2022 in a group of selected experts from nine CEE countries (an invitation was sent to 11 countries). A descriptive as well as statistical analysis was conducted to determine statistical significance, correlations, and Cohen's κ coefficients between the drug or country characteristic and the positive recommendation or reimbursement of an ODs. Results: The proportion of reimbursed orphan drugs differed between countries, ranging from 17.7% in Estonia to 49.6% in Hungary (p<0.001). The odds that ODs were reimbursed were reduced in countries with 'strong' level of impact of drug safety and efficacy on reimbursement decisions (p=0.018), the presence of other additional specific clinical aspects (e.g., genomic data) considered in the reimbursement decision (p<0.001) and mandatory (without exception) safety assessments (p=0.004). The probability that ODs were reimbursed was increased in countries with 'moderate' level of impact of drug safety and efficacy on reimbursement decisions (p=0.018), when reimbursement decisions dependent on EMA registration status and orphan drugs designation (p<0.001), the presence of 'positive HTA recommendation guarantees reimbursement' policy (p<0.001), higher GDP per inhabitant (p=0.003), and higher health care expenditure (p<0.001). Conclusions: We found that there are differences between CEE countries in the reimbursement of orphan drugs and we identified aspects that may influence these differences. Safety, efficacy, and specific clinical aspects issues significantly influenced reimbursement decisions. Oncology drugs were the largest group of ODs and increased the chance of getting a positive recommendation. The higher GDP per inhabitant and health care expenditures per inhabitant were positive linked to the chance that an OD receives reimbursement.